2011
DOI: 10.1097/inf.0b013e3181efff54
|View full text |Cite
|
Sign up to set email alerts
|

Timing of the Availability and Administration of Influenza Vaccine Through the Vaccines for Children Program

Abstract: the VFC program is critical to ensuring financially vulnerable children have access to vaccination. Manufacturers, distributors, and public health officials should deliver VFC influenza vaccine to providers as quickly as possible. Pediatric healthcare providers should increase efforts to vaccinate all populations, especially the VFC population, in later months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…VFC-eligible children who visit the practice before supplies arrive often leave unvaccinated and may not return later in the season to be vaccinated. Although the difference in delivery dates is decreasing, studies have reported that VFC vaccines arrive 2-4 weeks later than commercial supplies, which results in lower two dose compliance rates [32, 33]. Intervention practices rated early delivery of vaccine supplies as the most effective strategy available to them during the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…VFC-eligible children who visit the practice before supplies arrive often leave unvaccinated and may not return later in the season to be vaccinated. Although the difference in delivery dates is decreasing, studies have reported that VFC vaccines arrive 2-4 weeks later than commercial supplies, which results in lower two dose compliance rates [32, 33]. Intervention practices rated early delivery of vaccine supplies as the most effective strategy available to them during the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the majority of influenza vaccinations have been administered between October and December [8][9][10][11]. In 2007, the ACIP recommended initiation of seasonal influenza vaccination as soon as vaccines became available [12].…”
Section: Introductionmentioning
confidence: 99%
“…12 Although reminder-recall systems that notify families that their child needs a vaccine are widely recommended, 13,14 traditional strategies implemented via mail or telephone have had limited to no efficacy in urban, low-income, and minority populations [15][16][17] who are also at high risk for undervaccination. 18,19 We recently demonstrated the effectiveness of using text message reminders for first influenza vaccine doses in this population. 20 However, the impact of such reminders on return for a second needed dose is unknown.…”
Section: What This Study Addsmentioning
confidence: 99%